Causes of pulmonary granulomas: a retrospective study of 500 cases from seven countries. Issue 1 (19th October 2011) - Mukhopadhyay, Sanjay; Farver, Carol F; Vaszar, Laszlo T; Dempsey, Owen J; Popper, Helmut H; Mani, Haresh; Capelozzi, Vera L; Fukuoka, Junya; Kerr, Keith M; Zeren, E Handan; Iyer, Venkateswaran K; Tanaka, Tomonori; et al.
Abstract : Background: The frequencies of various causes of pulmonary granulomas in pathological material are unknown, as is the influence of geographical location on aetiology. The aim of this study was to identify the causes of pulmonary granulomas in pathological specimens, to define their frequencies, and to determine whether these causes vary by geographical location. Methods: 500 lung biopsies and resections containing granulomas were reviewed retrospectively by expert pulmonary pathologists from 10 institutions in seven countries. Fifty consecutive cases from each location were assigned a diagnosis based on histological features and available clinical/microbiological data. Results: A specific cause was identified in 58% of cases (290/500), most commonly sarcoidosis (136, 27%) and mycobacterial or fungal infections (125, 25%). Mycobacteria were identified in 19% of cases outside the USA versus 8% within the USA. In contrast, fungi accounted for 19% cases in the USA versus 4% in other locations. Fungi were mostly detected by histology, whereas most mycobacteria were identified in cultures. In 42% of cases (210/500) an aetiology could not be determined. Conclusions: Across several geographical settings, sarcoidosis and infections are the most common causes of pulmonary granulomas diagnosed in pathological specimens. Fungi are more commonly identified than mycobacteria in the USA, whereas the reverse is true in other countries. A definite aetiology cannot be demonstrated in more than a third of all cases of pulmonary granulomas, even after histological examination. These findings highlight the need to submit material for histology as well as cultures in all cases in which granulomatous disease enters the differential diagnosis.